Reliability and Factor Structure of the Westside Test Anxiety Scale among University Students - Prashanth, Talwar Yadar; Matheiken, Shevonne; Julia Ai Cheng, Lee; Surena, Binti Sabil (Mangalore, South India, 2019)
The Westside Test Anxiety Scale (WTAS) is a widely-used screening instrument for assessing test anxiety impairments in educational settings. However, psychometric properties of this measure have not been established adequately. Therefore, the main objective of this study was to evaluate the factor structure and measurement invariance of the WTAS. Data for the cross-sectional study was collected from a convenience sample of 218 undergraduate students enrolled in a public university in Malaysia. Construct validity was investigated by Exploratory Factor Analysis (EFA). Confirmatory Factor Analysis (CFA) was used to test two models (original structure and EFA structure). Also, multiplegroup invariance was analyzed in order to determine the extent to which the factor structure was comparable across gender. Results of CFA indicated that both models met all the preestablished fit criteria. There was however, more support for the re-organized two-factor EFA model, with high reliability values. Multi-group CFA demonstrated measurement invariance across gender. Findings from the present study indicate that the WTAS could serve as a screening tool to detect test anxiety among students.